Biomechanical Structure Specifics of the Javelin Throwing Technique of elite Athletes - Olexander Klimashevsky (Lesya Ukrainka Volyn National University, 2018)
The relevance of the research. At the current  stage of sports science development , the most promising direction for increasing sport results is that focuses on the maximum usage of the qualitative training process characteristics , reserves search of athletes' technical skill  improvement , methods and means of technical training, maximal realization of individual congenital and acquired inclinations of athletes. Statement of the Problem. The highest quality in the tmotor actions  technique improvement is achieved through the usage of biomechanical analysis  which is  based on the studying  of  biomechanical structures  using  modern electrooptical  systems of registration and analysis of  movements with the subsequent development of model indicators. The Purpose and Methods of Research. The aim of this work is to analyze the peculiarities of the biomechanical structure of the javelin throwing technique by elite athletes. Research methods : analysis of scientific and methodical literature, video, biomechanical analysis and  methods of mathematical statistics. Results and Key Conclusions. The analysis of the javelin throwing technique of highly qualified athletes is carried out. In the experiment four javelineers participated - masters of sport of the international class. With the help of video shooting and biomechanical analysis quantitative characteristics of the biomechanical structure of the throwing javelins technique of highly qualified athletes are obtained. The indexes that influence the javelin flight range in the phases of the previous run, final run and final effort are studied. The temporal, spatial and spatial-temporal characteristics of the technique of motor activity is analyzed. The obtained data is planned to be used for constructing models of the biomechanical structure of the javelin throwing technique. The indicators of the biomechanical structure of the javelin throwing technique discovered by highly qualified athletes can be used as sample models for athletes of lower qualification. Prospects for further research are the study of the biomechanical structure of the equipment of qualified athletes and the discriminatory features revealed in the technique of athletes of different qualifications, with the aim of further improving the javelin throwing technique of the qualified athletes.